2001
DOI: 10.1128/jvi.75.23.11935-11938.2001
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of EAV-HP Ancient Endogenous Retroviruses within the Chicken Population

Abstract: Avian leukosis virus subgroup J (ALV-J), an exogenous avian retrovirus, is thought to have evolved by recombination with the highly identical env gene of the endogenous avian retrovirus EAV-HP. Embryonic expression of EAV-HP env has been suggested to be associated with the induction of immunological tolerance, a feature observed in a significant proportion of meat-type chickens infected with ALV-J. In support of this hypothesis, we demonstrate that EAV-HP loci, some of which could be associated with tolerance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
1
7
1
Order By: Relevance
“…The close genomic proximity (23 bp) of the different insertion sites, observed in Mapuche fowl and Dongxiang chicken, suggests a possible integration site preference for EAV-HP, as has been suggested for several retroviruses [22]. Active ongoing insertion and segregation of EAV-HP in chicken populations have been shown with a typical prevalence of 10 to 15 copies per genome [23], [24]. Such EAV-HP genome dynamism is thought to play a recombinant role in the emergence of exogenous avian retrovirus ALV-J due to a uniquely similar env sequence with the ALV-J prototype HPRS-103 [23].…”
Section: Discussionmentioning
confidence: 68%
“…The close genomic proximity (23 bp) of the different insertion sites, observed in Mapuche fowl and Dongxiang chicken, suggests a possible integration site preference for EAV-HP, as has been suggested for several retroviruses [22]. Active ongoing insertion and segregation of EAV-HP in chicken populations have been shown with a typical prevalence of 10 to 15 copies per genome [23], [24]. Such EAV-HP genome dynamism is thought to play a recombinant role in the emergence of exogenous avian retrovirus ALV-J due to a uniquely similar env sequence with the ALV-J prototype HPRS-103 [23].…”
Section: Discussionmentioning
confidence: 68%
“…This small proportion (approximately 8%) is suggestive of a genotype with both genes recessive and provides the first indication that ALV-J tolerance might be due to two unlinked yet interacting gene products. This result contradicts the previous hypothesis that tolerance develops from the expression of EAV-HP env peptides that provide epitopes for MHC presentation that are shared with ALV-J during lymphocyte negative selection (30)(31)(32)37 From a comparison of the two animal experiments described here, the development of immunological tolerance and development of the myeloid leukosis tumors typically induced by ALV-J appear to be determined by distinct genetic elements. None of the immunologically tolerant line 15I layer birds developed tumors throughout the duration of the experiment despite the fact that this line was originally selected for its susceptibility to lymphoid leukosis induction by other ALV subgroups (3).…”
Section: Discussioncontrasting
confidence: 55%
“…In our previous attempts to characterize EAV-HP proviruses from various chicken lines, particularly from meat-type chicken lines in which ALV-J may have arisen, we were unable to identify viruses that had intact provirus structures (5Ј-LTR-gag-pol-env-LTR-3Ј). Subsequent studies to find out the distribution of three specific provirus deletion loci revealed that these elements were segregating within the chicken population (32). This suggested that moreintact genomes may have eluded detection due to the chance selection of embryos from the outbred meat-type chicken lines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations